Toxicology of micro and nanoplastics: risk of toxic at low dose and epigenetic changes - Montero-Campos, Virginia (2023)
The toxicological risks associated with nano and microplastics (NMP) are directly related to the oral ingestion intake of these particles, generally by fragmentation of packaging and their consequent presence in natural food products, drinking water and other articles that are basic products in our daily life. The particles whose destination is the ocean, can consequently be ingested by marine species, putting food security at risk, having access to the highest levels of the food chain. Nanoplastics (NP), due to their small size and ease of movement, are related to the production of reactive oxygen species (ROS) within the cell, which is directly associated with the possible carcinogenic processes. In response to constant exposure to microplastics (PM) we can find associated with manufacturing, the presence of plasticizing substances and stabilizers such as Bisphenol A and Pthalates, which at very low doses are associated with endocrine disruption, that is, hormone replacement in the body due to structural resemblance, which leads to metabolic alterations with manifestations throughout life, including transmission to offspring due to associated epigenetic effects. One of the problems with these substances is the effect of low doses, since they have a behavior called “non-monotonic dose response curve” (NMDRC) for which adverse effects can be observed at or below the internationally accepted reference doses.